A randomized trial of intensified vs. standard dosing for enteric-coated mycophenolate sodium in de novo kidney transplant recipients: results at 1 year - Arns, Wolfgang; Sommerer, Claudia; Glander, Petra; Ariatabar, Toofan; Porstner, Martina; May, Christoph; Paulus, Eva-Maria; Shipkova, Maria; Fischer, Wolfgang; Liefeldt, Lutz; Hackenberg, Ruth; Schemmer, Peter; et al. (Clinical nephrology, 2013)
In a 6-month prospective, openlabel, multicenter study, 128 de novo kidney transplant patients receiving cyclosporine (CsA) and steroids were randomized to an intensified regimen of enteric-coated mycophenolate sodium (EC-MPS) or to a standard EC-MPS regimen to Week 6 posttransplant, after which the regimen was identical. In a follow-up study to Month 12 post-transplant (49 intensified regimen, 52 standard regimen), the reduced rate of BPAR observed at Month 6 (intensified regimen 3.2%, standard regimen 16.9%, p = 0.016) was maintained at Month 12 (4.8% vs. 18.5%, p = 0.026). Estimated GFR (Cockcroft-Gault) at Month 12 was comparable in the intensified group (mean (SD) 54.8 (22.9) ml/min) vs. the standard group (mean (SD) 57.5 (23.6) ml/min, p = 0.83). The incidence of adverse events and serious adverse events at Month 12 was similar in both treatment groups, although adverse events with a suspected relation to study drug were reported in 69.8% and 50.8% of patients in the intensified and standard regimen groups, respectively (p = 0.032). Infections and hematological parameters were similar between groups. In conclusion, an early regimen of intensified EC-MPS with CsA and steroids achieves a low rate of BPAR over the first year after kidney transplantation with similar renal function to a standard regimen, and without a clinically relevant impact on safety.
Gesehen am 26.10.2020